The effect of pre-exercise caffeine loading on body composition, blood parameters and resting pulse rate in women - Murat Bekleyiş Apaydın; Rüçhan İri (ROL Spor Bilimleri Dergisi)
The purpose of our study is to determine the impact of caffeine consumption before exercise activities on the body composition, rest pulsebpm, hemoglobinmg/dL, glucosemg/dL values of women who have an exercise history of at least 3 years. A total of 28 healthy women willingly participated in our study, consisting of the Step-aerobic group (Group A, N=10); Zumba (Group B, N=9), and the control group (Group C, N=9). In our study, caffeine xanthine was applied to the Step aerobics (6gr) and Zumba groups (3gr) 60 minutes before exercise respectively. On the other hand, no caffeine application was conducted in the control group. In the statistical analysis of our study, the SPSS 24 version program was utilized. The paired sample t-test was utilized for the comparison of inter-group pre-test and post-test averages, while One Way Anova was utilized for group comparisons. When inter-group comparisons were conducted in the study, the data that differences occurred in Group A, BW (kg), BMI (kg/m2), glucose(mg/dL); Group B, glucose(mg/dL), rest pulse(bpm) was reached (p<0.05). When the group averages were compared, the finding that the body composition and rest pulse(bpm) measurements demonstrated differences was reached (p<0.05). In conclusion, the finding that pre-exercise caffeine intake leads to decreases in body composition measurements and increases in the averages of blood glucose(mg/dL), and rest pulse(bpm) was reached.